Exposure to Community Violence, Affiliations With Risk-Taking Peer Groups, and Internet Gaming Disorder Among Chinese Adolescents: The Moderating Role of Parental Monitoring - Liang, Qiao; Yu, Chengfu; Chen, Quanfeng; Xie, Xiaodong; Wu, Han; Xing, Jintao; Huang, Shihua; Dou, Kai (Frontiers in Psychology, 2019)
Among adolescents, exposure to community violence (ECV) has been consistently linked to problem behaviors such as internet gaming disorder (IGD). However, the associated risk and protective factors have not been adequately explored in past studies. Therefore, in accordance with the risk-buffering model and social development model, this study aimed to test whether parental monitoring moderated the relationship between ECV and IGD among adolescents, and whether this moderating effect was mediated by affiliations with risk-taking peer groups. A sample of 2,423 Chinese middle-school students anonymously responded to questionnaires that assessed ECV, IGD, affiliations with risk-taking peer groups, and parental monitoring. The results of structural equation modeling revealed that the interaction between ECV and parental monitoring negatively related to IGD among adolescents. Specifically, the positive relationship between ECV and IGD was stronger for adolescents who reported low levels of parental monitoring than for those who reported high levels of parental monitoring. Moreover, this moderating effect was mediated by affiliations with risk-taking peer groups. These results suggest that parental monitoring is an important protective factor that can mitigate the risk of IGD among adolescents who have been exposed to community violence. Accordingly, these findings serve as an empirical base upon which prevention and intervention strategies that are aimed at mitigating the risk of IGD among adolescents can be developed.